A Regulations’ Survey for the Wireless Telecommunications Deployment in Colombia (2016)
This paper describes the current wireless telecommunications infrastructure deployment regulations in Colombia. It also refers to the possible effects that this infrastructure could cause to the country`s health and environment. similarly, the results obtained show a comparison between the Argentina’s current regulations, one of the most relevant researchescarried out and the Colombian case. finally, some recommendations are proposed that can be considered in the project of regulations applicable in Colombia for the ensuring purpose that the non-ionizing radiation generated by wireless communications systems do not have effects on health and the environment.